From Alexa to Siri and the GDPR: The gendering of Virtual Personal Assistants and the role of Data Protection Impact Assessments. Issue 36 (April 2020) - Loideain, Nóra Ni; Adams, Rachel
Abstract: With female names, voices and characters, artificially intelligent Virtual Personal Assistants such as Alexa, Cortana, and Siri appear to be decisively gendered female. Through an exploration of the various facets of gendering at play in the design of Siri, Alexa and Cortana, we argue that this gendering of VPAs as female may pose a societal harm, insofar as they reproduce normative assumptions about the role of women as submissive and secondary to men. In response, this article turns to examine the potential role and scope of data protection law as one possible solution to this problem. In particular, we examine the role of data privacy impact assessments that highlight the need to go beyond the data privacy paradigm, and require data controllers to consider and address the social impact of their products.